Participation Barriers to Youth Civic Engagement in Social Media - Brandtzæg, Petter; Haugstveit, Ida Maria; Lüders, Marika; Følstad, Asbjørn (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Organizations aiming to foster civic engagement, such as government bodies, news outlets, political parties, and NGOs, struggle to purposefully use social media to engage young people. To respond to this challenge we conducted five group-interviews with 27 youth, 16–26 years, about their experiences of and barriers to civic engagement in social media. Our paper contributes to identifying specific participation barriers that young people experience concerning social media civic engagement, and how organizations should work to overcome these barriers.